Comparative Analysis of Liquid Chromatography-Tandem Mass Spectrometry and Radioimmunoassay in Determining Plasma Aldosterone Concentration and Plasma Renin Activity for Primary Aldosteronism Screening - So Yoon Kwon; Kyeong-Jin Kim; Soo-Youn Lee; Jae Hyeon Kim (Endocrinology and Metabolism)
Liquid chromatography-tandem mass spectrometry (LC-MS/MS) accurately measures plasma aldosterone concentration (PAC), but its correlation with radioimmunoassay (RIA), equivalent RIA levels, and optimal cutoff for PAC and aldosterone-to-renin ratio (ARR) in primary aldosteronism (PA) screening have not been determined in a Korean population. Our study of 127 patients who underwent diagnostic testing for PA showed that the LC-MS/MS and RIA methods have good correlation, with a mean bias of 29.3% for PAC. An LC-MS/MS PAC level of 11.7 ng/dL was equivalent to an RIA PAC level of 15 ng/dL. Receiver operating characteristic curve analysis showed that an LC-MS/MS PAC level of 10.3 ng/dL and LC-MS/MS ARR level of 20.0 provided sensitivity of 73.1% with a specificity of 57.3% and sensitivity of 92.3% with a specificity of 14.7%, respectively. When the LC-MS/MS method is used for PA screening, an adjustment of cutoff values is necessary.